2017
DOI: 10.3803/enm.2017.32.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Postoperative Diabetes Insipidus after Pituitary Surgery

Abstract: BackgroundDetermining risk factors for diabetes insipidus (DI) after pituitary surgery is important in improving patient care. Our objective is to determine the factors associated with DI after pituitary surgery.MethodsWe reviewed records of patients who underwent pituitary surgery from 2011 to 2015 at Philippine General Hospital. Patients with preoperative DI were excluded. Multiple logistic regression analysis was performed and a predictive model was generated. The discrimination abilities of the predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…2,9,18 Regarding surgical aspects, we did not nd any association with DI, and in the literature, there is no evidence that re-operation increases the incidence of transient or permanent DI. 20,26,29 Concerning the endoscopic or microscopic technique, the incidence of DI varies according to the series studied, although no signi cant difference was observed in our cohort. 26 According to some studies, a variation in serum sodium, either in percentage or absolute value, could be associated with an increased risk of developing DI.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2,9,18 Regarding surgical aspects, we did not nd any association with DI, and in the literature, there is no evidence that re-operation increases the incidence of transient or permanent DI. 20,26,29 Concerning the endoscopic or microscopic technique, the incidence of DI varies according to the series studied, although no signi cant difference was observed in our cohort. 26 According to some studies, a variation in serum sodium, either in percentage or absolute value, could be associated with an increased risk of developing DI.…”
Section: Discussionmentioning
confidence: 59%
“…However, Joshi et al described being male as a risk factor. 27 Furthermore, several studies 9,10,[26][27][28][29][30] found that sex is not associated with the development of DI. In our study, younger age was associated with a higher risk of presenting DI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Clement et al, DI occurred in more than 2.6% of their cohort. DI is typically diagnosed immediately after neurosurgery for low-grade gliomas or germ cell tumors (19).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, everyone is encouraged to vaccinate themselves because it is safe to build protection against the virus and provide immunity after complete vaccine administration [44] . Aside from all the treatments presented, herbal medicines and natural products such as virgin coconut oil are observed to have antioxidant, anti-inflammatory, antiviral, and antifungal properties, which could benefit COVID-19 patients [45] . VCO contains a wide variety of phytochemical compounds capable of disintegrating the virus envelope, preventing the viral proteins in binding to the host membrane, and inhibiting the late maturation stage in the virus replication cycle [7] .…”
Section: Vaccinesmentioning
confidence: 99%